Plant-Derived Essential Oils; Their Larvicidal Properties and Potential Application for Control of Mosquito-Borne Diseases: - Osanloo, Mahmoud; Sedaghat, Mohammad Mehdi; Sanei-Dehkordi, Alireza; Amani, Amir (Galen Medical Journal, 2019)
Mosquito-borne diseases are currently considered as important threats to human health in subtropical and tropical regions. Resistance to synthetic larvicides in different species of mosquitoes, as well as environmental pollution, are the most common adverse effects of excessive use of such agents. Plant-derived essential oils (EOs) with various chemical entities have a lower chance of developing resistance. So far, no proper classification based on lethal concentration at 50% (LC50) has been made for the larvicidal activity of EOs against different species of Aedes, Anopheles and Culex mosquitoes. To better understand the problem, a summary of the most common mosquito-borne diseases have been made. Related articles were gathered, and required information such as scientific name, used part(s) of plant, target species and LC50 values were extracted. 411 LC50 values were found about the larvicidal activity of EOs against different species of mosquitoes. Depending on the obtained results in each species, LC50 values were summarized as follows: 24 EOs with LC50 < 10 µg/mL, 149 EOs with LC50 in range of 10- 50 µg/mL, 143 EOs having LC50 within 50- 100 µg/mL and 95 EOs showing LC50 > 100 µg/mL. EOs of Callitris glaucophylla and Piper betle against Ae. aegypti, Tagetes minuta against An. gambiae, and Cananga odorata against Cx. quinquefasciatus and An. dirus having LC50 of ~ 1 µg/mL were potentially comparable to synthetic larvicides. It appears that these plants could be considered as candidates for botanical larvicides. [GMJ.2019;8:e1532]